Gel-Based Luminescent Conductive Materials and Their Applications in Biosensors and Bioelectronics - Jiajin Qi (MDPI AG, 2021)
The gel is an ideal platform for fabricating materials for bio-related applications due to its good biocompatibility, adjustable mechanical strength, and flexible and diversified functionalization. In recent decades, gel-based luminescent conductive materials that possess additional luminescence and conductivity simultaneously advanced applications in biosensors and bioelectronics. Herein, a comprehensive overview of gel-based luminescent conductive materials is summarized in this review. Gel-based luminescent conductive materials are firstly outlined, highlighting their fabrication methods, network structures, and functions. Then, their applications in biosensors and bioelectronics fields are illustrated. Finally, challenges and future perspectives of this emerging field are discussed with the hope of inspire additional ideas.